Studies on Poly(propylene fumarate-co-caprolactone diol) Thermoset Composites towards the Development of Biodegradable Bone Fixation Devices - Jayabalan, M. (International Journal of Biomaterials, 2009)
The effect of reinforcement in the cross-linked poly(propylene fumarate-co-caprolactone diol) thermoset composites based on Kevlar fibres and hydroxyapatite was studied. Cross-linked poly(propylene fumarate-co-caprolactone diol) was also studied without any reinforcement for comparison. The reinforcing fibre acts as a barrier for the curing reaction leading to longer setting time and lesser cross-link density. The fibre and HA reinforced composites have almost the same compressive strength. Nonreinforced material undergoes greater degree of swelling. Among the reinforced materials, the hydroxyapatite reinforced composite has a much higher swelling percentage than the fibre reinforced one. The studies on in vitro degradation of the cured materials reveal hydrolytic degradation in Ringer's solution and PBS medium during aging. All the three materials are found to swell initially in Ringer's solution and PBS medium during aging and then undergo gradual degradation. Compression properties of these cross-linked composites increase with aging; HA reinforced composite has the highest compressive strength and compressive modulus, whereas the aged fibre-reinforced composite has the least compressive strength and modulus.